Three new jatrophane polyesters and anti proliferative constituents from Euphorbia tuckeyana - Duarte, Noelia (2015)
Three new jatrophane diterpene polyesters named tuckeyanols A and B and euphotuckeyanol, as well as ten known compounds, helioscopinolides A, 13, D and E, naringenin, aromadendrin, coniferaldehyde, 4,20-dideoxy-5-hydroxyphorbol 12,13-diisobutyrate, 4,20-dideoxy-5-hydroxyphorbol 12-benzoate-13-isobutyrate and dehydrodiconiferyl diacetate, were isolated from the methanolic extract of Euphorbia tuckeyana. Their structures were elucidated by physical and spectroscopic methods including 1 D and 2 D homo- and heteronuclear NMR techniques (COSY, HMQC, HMBC and NOESY), and HR-mass spectrometry. Four of the isolated compounds were investigated for their anti proliferative activity in three human gastrointestinal cancer cell lines: gastric (EPG85-257), pancreatic (EPP85-181) and colon (HT-29) carcinomas. Three of them have showed to be moderate inhibitors of the growth of gastric and pancreatic tumor cell lines.